2009
DOI: 10.1021/jp907223t
|View full text |Cite
|
Sign up to set email alerts
|

On the Energetics of ATP Hydrolysis in Solution

Abstract: ATP hydrolysis is the driving force of many life processes, yet the exact nature of and contributions to the energetics of this reaction are far from being clear. In particular, it is unclear how much of the driving force of this reaction is due to the separation of the already dissociated ADP + P(i) moieties rather than to the chemical event. This fundamental issue is explored here by ab initio calculations that use different solvation models, and it is found that, while the calculations are sensitive to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 55 publications
2
65
0
Order By: Relevance
“…Some workers have suggested that the major source of the energy release is the conversion of the free energy of ATP binding into elastic strain, which is subsequently released by a coordinated and tightly coupled conformational mechanism (6). It was also postulated that the energy conversion involves an inertial energy release (12), whereas our works (13,14) have suggested that the energetics is associated with the electrostatic work, and the origin of the free energy change involves a significant contribution from the charge separation in solution outside the ATPase active sites. Furthermore, biochemical and structural studies have provided a molecular model for the action of ATPases (1)(2)(3)(4), and remarkable phenomenological analyses (6,7) indicated what are the conditions for effective action.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Some workers have suggested that the major source of the energy release is the conversion of the free energy of ATP binding into elastic strain, which is subsequently released by a coordinated and tightly coupled conformational mechanism (6). It was also postulated that the energy conversion involves an inertial energy release (12), whereas our works (13,14) have suggested that the energetics is associated with the electrostatic work, and the origin of the free energy change involves a significant contribution from the charge separation in solution outside the ATPase active sites. Furthermore, biochemical and structural studies have provided a molecular model for the action of ATPases (1)(2)(3)(4), and remarkable phenomenological analyses (6,7) indicated what are the conditions for effective action.…”
mentioning
confidence: 70%
“…Studies of the energetics of the reactant and product in different states of the F1-ATPase subunits included microscopic free energy calculations, using molecular mechanical approaches (17), that did not actually simulate the chemical process. At present, the semimacroscopic linear response approximation calculations of the chemical step in different subunit states (13) seems to yield the most reliable results when we also consider a careful analysis of the reference solution reaction (14). Although it is possible to obtain a reasonable insight on the energetics of the chemical steps within each subunits (13,17), the main challenge is to obtain an insight on the overall energy change in the complete ATPase system, including the barriers for conformational changes, and the overall energetics of the rotary process.…”
mentioning
confidence: 99%
“…Also, the applications of this approach towards predicting the solvation free energies of small biomolecules in water and calculating the pKas of protein side chains have been demonstrated in Refs. [60] and [61] respectively. In this approach, the system is divided into two different regions: of main interest to us is the part of the system which changes (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, phosphate esters have been the subject of extensive experimental 3,6-13 and theoretical [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] studies (though the precise mechanisms of both the solution and enzyme catalyzed reactions remain controversial, see e.g. [6][7][8]12,14,15,25,26,29,[33][34][35] ).…”
Section: Introductionmentioning
confidence: 99%